A comparative study between a commercially produced retration cord and the U.P.C.D. produced retration cord - Tiu, Elnora
A total of 90 samples of central incisors were used, utilizing the labial gingival sulcus as investigation site. 15 central incisors were used for each type of retraction cord. The unretracted labial gingival sulcus served as control, while the retracted gingival as the experimental site. Results were subjected to a one way analysis of variance which concluded that there was no significant difference among the three retraction cords used.